Temporal host–symbiont dynamics in community contexts: Impacts of host fitness and vertical transmission efficiency on symbiosis prevalence - Gundel, Pedro Emilio (2024)
Symbiotic associations play a role in plant ecology and evolution, but the outcome of the interaction depends on the life-history traits of the partners and the environmental context. Although symbiosis with vertically transmitted microorganisms should result in mutualism, it is not clear how the transmission process aligns with the outcome of the context-dependent symbiosis. For 3 years, we sampled individuals of an annual plant species that forms symbiosis with a vertically transmitted fungal endophyte, in paired stands of two contrasting vegetation communities (humid mesophytic meadows [HMM]: productive/low stress, and humid prairies [HP]: less productive/high stress). We estimated the prevalence of symbiosis at the population level, and the fitness of the plant, the symbiotic status and vertical transmission efficiency at the individual level. Over 3 years, the prevalence of symbiosis was ≈100% in HMM and ≈75% in HP. Plant fitness was very low and high in years with precipitation below and above the yearly mean, respectively. The higher fitness of endophyte-symbiotic plants was evident in the HMM and high precipitation years. Vertical transmission of endophytes was higher in HMM (≈96%) compared to HP (≈93%) and was not related to plant fitness. Despite transmission inefficiencies in HP, changes in prevalence within the growing season (from seeds to the final plant stand) suggest a fitness advantage for symbiotic plants. Vertical transmission is expected to promote mutualism as it aligns partners' fitness. Although symbiotic plants showed higher fitness and the probability of transmission failures was higher among low-fitness plants, the variation in transmission efficiency between plants and vegetation communities was not related to the fitness of the individual host. Our study provides evidence that context-dependent vertical transmission efficiency and endophyte-mediated fitness advantages interact complexly to determine the prevalence of symbiosis in populations that occur in contrasting vegetation communities.